Modeling and Numerical Prediction on Mechanical Behaviors of Hybrid Fiber Reinforced Polymer Bio Composites Using Fuzzy Logic Algorithm - Vinoth Viswanathan; Sathiyamurthy Subbarayan; Ananthi Narayanaswamy; Devi Panneerselvam; Prabhakaran Jayasankar (Mechanics of Advanced Composite Structures)
The present study investigates the mechanical behaviors of hybrid fiber-reinforced polyester composites in developing a new strengthened material. The experiments were planned as per the design of experiments, the selected input parameters were fiber length (mm), NaOH treatment (%), and fiber weight (%) and the output parameters were tensile, flexural, and impact strength conditions. A Non-Linear Regression Modelling (NLRM) and Fuzzy logic model have been designed to predict and analyze the mechanical properties in unknown test conditions. Every input factor was categorized into three linguistic descriptors, while each output factor was classified into three linguistic categories. A triangular membership function was employed to define all these variables. The effectiveness of the nonlinear regression analysis and fuzzy logic model was evaluated through confirmatory experiments. The model predicted the mechanical results with an error of 7.19%, 5.38%, and 2.33% respectively. The proposed approach can significantly simplify real-life multi-response optimization problems, thereby reducing fabrication costs and enhancing composite fabrication efficiency.